Factors affecting the high rate of sports injuries in football pitches In sports complexes in some states of Algeria - bencherif, Yacine (sports creativity, 2025)
The study aimed to find out the factors affecting the increasing of sports injuries in football pitches within neighborhood sports complexes , and we will try through this field research to highlight the contributions of neighborhood sports complexes in the promotion of sports and physical activities, especially Football, as it attracts the largest number of practitioners of different ages categories therefore it has role in providing the necessary possibilities and means and the appropriate atmosphere to conduct trainings and competitions in acceptable conditions that take into account the safety and security of practitioners in this type of flooring specificity of compacted artificial soil which is greatly affected as it is defined by the act of frequent exploitation and weather factors. In this study, the researcher used the questionnaire, which was distributed to a sample of (45) individuals, officials of sports complexes, through three (03) states, namely, Laghouat , Djelfa and M'sila , and the results concluded that there are imbalances in the methods of completion of football stadiums and their differences between them in terms of design and this from one sports boat to another, and that the human and material capabilities available at the level of these facilities are insufficient to provide and ensure periodic maintenance .